Nipple-Sparing Mastectomy: Reliability of sub-areolar sampling and frozen section in predicting occult nipple involvement in breast cancer patients. Issue 11 (November 2018) - D'Alonzo, Marta; Pecchio, Silvia; Campisi, Paola; De Rosa, Giovanni; Bounous, Valentina Elisabetta; Villasco, Andrea; Balocco, Paolo; Biglia, Nicoletta
Abstract: Introduction: The oncological safety of nipple-areolar complex (NAC) preservation is a concern in the mastectomies performed for cancer indication. The detection of tumor cells during the intraoperative frozen section examination (IE) of sub-areolar/nipple tissue (SAT) leads to the removal of NAC, but frequently the final histology of the nipple is negative for malignancy. This study aims to evaluate the accuracy of SAT examination in predicting occult NAC involvement in case of Nipple-Sparing Mastectomy (NSM). Methods: The study includes 76 NSM. We evaluated the concordance between histopathologic features of frozen and paraffin-embedded SAT sections. Moreover, we examined the "true margin" (TM), defined as the measurement of the distance between the tumor margin and the edge of the SAT. A margin >1 mm was considered negative. Results: In 26/76 cases the IE of the SAT was positive. At the final histology, the NAC was negative in 57.7% of cases. The concordance between frozen and paraffin section examination of the SAT was 92.1%. The three false-positives were low-grade DCIS at the IE, and negative or DIN1a on permanent section. A negative TM seems to predict for a negative NAC (6/6). Conclusions: The detection of a low-grade DCIS at the IE of the SAT may not be confirmed at the permanent section examination; we recommend caution in removing the NAC in these cases. The evaluation of the TM may improve the accuracy of SAT analysis in predicting occult NAC involvement; in our series, a TM wider than 1 mm correlates with a negative NAC.